Comparison of cloud computing providers for development of big data and internet of things application - Muhammad Fajrul Falah; Yohanes Yohanie Fridelin Panduman; Sritrusta Sukaridhoto; Arther Wilem Cornelius Tirie; M. Cahyo Kriswantoro; Bayu Dwiyan Satria; Saifudin Usman (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The improved technology of big data and the internet of things (IoT) increases the number of developments in the application of smart city and Industry 4.0. Thus, the need for high-performance cloud computing is increasing. However, the increase in cloud computing service providers causes difficulties in determining the chosen service provider. Therefore, the purpose of this study is to make comparisons to determine the criteria for selecting cloud computing services following the system architecture and services needed to develop IoT and big data applications. We have analyzed several parameters such as technology specifications, model services, data center location, big data service, internet of things, microservices architecture, cloud computing management, and machine learning. We use these parameters to compare several cloud computing service providers. The results present that the parameters able to use as a reference for choosing cloud computing for the implementation of IoT and big data technology.